Treatments for Non-Small-Cell Lung Cancer: The Multiple Options for Precision Medicine - Elvire Pons-Tostivint; Jaafar Bennouna (Current Oncology, 2022)
In recent years, advances in molecular diagnostics have transformed the management of advanced non-small-cell lung cancer (NSCLC), allowing for increasingly personalized approaches [...]